AAA ‐ autonomous anonymous user authentication and its application in V2G. (9th October 2017) - Braeken, A.; Touhafi, Abdellah
Summary: Cloud computing offers a simple way to provide access to servers, storage, databases, and a broad set of application services over the Internet. Its popularity is growing spectacularly. Consequently, there is a need for strong authentication schemes, offering besides data privacy also identity privacy during these actions. Therefore, this paper presents 2 user‐friendly protocols, called the autonomous, anonymous, and authentication—AAA1 and AAA2—schemes, able to derive the required security material at user's side without the need of a secure channel between user and registration center. The protocol AAA2 has the added functionality to guarantee unforgeability and non‐repudiation of the request. Only simple elliptic curve operations, together with hashes and symmetric key encryptions are used. The proposed protocols are 2‐factor based, requiring the knowledge of the password and the possession of a correctly installed smartphone, and are very efficient to be executed on the smartphone because of a small amount of computations. As an application, we show how AAA1 can be utilized in a communication protocol for monitoring and AAA2 for charging and discharging of electrical vehicles with the smart grid. Moreover, these proposed solutions allow a much better performance, compared with the state of the art protocols in this field.